The Roman Army and the Economy - Erdkamp, Paul (Brill Book Archive Part 1, ISBN: 9789004472495., 2002)
Contents: PART ONE : SUPPLYING THE ROMAN ARMIES HERZ, P.: Die Logistik der kaiserzeitlichen Armee. Strukturelle Überlegungen. ERDKAMP, P.: The Corn Supply of the Roman Armies during the Principate (27 BC - 235 AD). CARRERAS MONTFORT, C.: The Roman military supply during the Principate. Transportation and staples. BLOIS, L. DE: Monetary policies, the soldiers' pay and the onset of crisis in the first half of the third century AD. PART TWO : COMMUNICATIONS AND TRANSPORT HAYNES, I.: Britain's First Information Revolution. The Roman army and the transformation of economic life. KISSEL, Th.: Road-building as a munus publicum. KOLB, A.: Army and transport. PART THREE : THE ROMAN WEST: HISPANIA, BRITANNIA AND GERMANIA DAVIES. J.L.: Soldiers, peasants, industry and towns. The Roman army in Britain. A Welsh perspective. WHITTAKER, C.R.: Supplying the army. Evidence from Vindolanda. FUNARI, P.P.A.: The consumption of olive oil in Roman Britain and the role of the army. WIERSCHOWSKI, L.: Das römische Heer und die ökonomische Entwicklung Germaniens in den ersten Jahrzehnten des 1. Jahrhunderts. REMESAL RODRIGUEZ, J.: Baetica and Germania. Notes on the concept of 'provincial interdependence' in the Roman Empire. KONEN, H.: Die ökonomische Bedeutung der Provinzialflotten während der Zeit des Prinzipates. PART FOUR : NORTH AFRICA AND THE EAST MORIZOT, P.: Impact de l'armée romaine sur l'économie de l'Afrique. ROTH, J.: The army and the economy in Judaea and Palestine. ALSTON, R.: Managing the frontiers. Supplying the frontier troops in the sixth and seventh centuries.